Kinerja pengering satu tungku penukar panas dengan energi sekam padi untuk mengeringkan pisang menggantikan pengeringan langsung matahari - Alit, I.B.; Susana, I.G.B. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2024)
The banana drying process for small farmers only uses the sun due to technological and cost limitations. The weakness of drying products is that they are very dependent on the weather. An alternative is to use a rice husk energy dryer because it is cheap and easy to obtain. The method involves converting rice husks into thermal utilizing a heat exchanger. The heat exchanger transfers heat from burning the husk to the drying chamber. Research was conducted to compare the temperature and drying time between sun drying and rice husk dryers. Apart from that, to determine the dryer's performance for drying bananas for a small-scale farmer. As a result, the rice husk energy dryer provides a shorter time than drying under the sun. To reduce the water content from 72% to a maximum of 40%, the time required for a rice husk energy dryer is 300 minutes, and 660 minutes for sun drying. The resulting temperature averages 55.11oC, while sun drying averages 29.02oC. In addition, the rice husk energy dryer produces a drying efficiency of 44.15%, which occurs at the beginning of drying and ends at 4.61%. This is a result of the high initial moisture content. During drying, the water content of the material evaporates, which impacts the energy absorption process by the banana from the dryer. The drying rate also followed this pattern: at the beginning, it was highest at 5.93 g/minute, and at the end, it was the lowest at 0.1 g/minute.